Evaluating the usability of an X-ray imaging system in forensic pathology - Mutswangwa, Christopher T (Division of Biomedical Engineering, 2019)
Post mortem imaging (PMI) is increasingly being adopted as an alternative to invasive autopsies in forensic pathology. PMI can be used as a sole technique or adjunct to an autopsy. The Lodox Xmplar-dr is an X-ray imaging system that has been adopted for use in PMI. The purpose of this study was to evaluate the perceived usability of this imaging system by focusing on the satisfaction of forensic pathologists in use of the system. Assessment of satisfaction was guided by the subjective satisfaction characteristics of likability, pleasure, comfort and trust. Incorporation of user needs into updated system designs may lead to greater perceived ease of use, acceptance and adoption, resulting in increased device utilisation. The study location was the Lodox Xmplar-dr installation site at the Salt River Forensic Laboratory, Cape Town. Five forensic pathologists were observed using the Xmplar-dr system and four were interviewed on their experience using the system. A qualitative research design which used thematic analysis with the aid of NVIVO11 qualitative data analysis software was used to extract key usability and satisfaction themes emerging from the data, to show the extent of user satisfaction. Two key themes emerged. These were categorised as forensic pathologist-related, which focused on the hedonistic and subjective aspects of their satisfaction with the system, and systemrelated, which centred on the satisfaction users derived from the system’s ability to meet their pragmatic and objective expectations in their use of the system. In general, the forensic pathologists were satisfied with the Xmplar-dr system and it exceeded their expectations. Pleasure was derived from the ability of the system to increase work throughput by reducing the need to perform a dissectional post-mortem unless it was deemed absolutely necessary, i.e. when cause of death could not be determined from the X-ray images generated by the system. Participants felt that the system was an indispensable device when performing post mortems. Likability came from the ease of learning to use the basic functions of the system; the study participants stated that the system aided them in determining cause of death and saved time, in line with the definition of the likability characteristic that is centred on the extent to which a user is satisfied with perceived achievements of pragmatic goals. Trust was derived from participants’ views that the system worked as intended, although there could be improvements in terms of robustness, reliability and the imaging system`s support services. Image manipulation on the human-computer interface (HCI) and image representation were concerns highlighted. Most functions could be performed through the system’s HCI rather than by manipulation of the body being examined; this increased the physical comfort satisfaction characteristic. The need for manual placement of bodies on the system`s table by assistants and the associated health consequences were however raised as a concern that diminished the comfort-in-use characteristic of satisfaction. Understanding the user experience of the forensic pathologists who use the Lodox Xmplar-dr system to perform post mortems enabled the identification of areas for improvement. The improvements may increase user satisfaction resulting in better utilisation of the imaging system. The insights gained may be useful for the design of other imaging systems used in forensic pathology.